How important is the frontline uniform toward employee’s self-efficacy? A case study of five-star hotel / Nurliyana Baharuddin and Mohd Raziff Jamaluddin - Baharuddin, Nurliyana; Jamaluddin, Mohd Raziff (Faculty of Hotel and Tourism Management, Universiti Teknologi MARA Cawangan Selangor, 2020)
In reality, uniform always represents pride, responsibility and also respect. It creates an image for the organization because the stakeholders will always associate uniform with the kind of services that they will receive. Even there are many significant findings on the importance of uniform toward self-efficacy, different scenario is observed in the hotel industry; where the literature discussing this issue is almost equal to none. How important is the uniform especially to the front-line operations remained to be answered? Hence, this study aimed to come out with a simple resolution of “Frontline uniform has an impact on employee’s self-efficacy.” The research used the five-star hotel segment as the case and studied the frontline staff. The research is quantitative where 253 respondents participated throughout two months of data collection by employing a snowball sampling technique. The data were analyzed using the PLSSEM where the data was grouped in the proposed model before several alterations were done to come out with the model of employee’s self-efficacy. The final model was able to provide an answer to the research questions where material, appropriateness, style, and functionality have a direct positive influence on the employee's self-efficacy of the five-star hotel segment. This study helped in filling the gap of the significant impact uniform has toward employee’s happiness in performing their roles as the ambassador of the hotel. Besides, the hotel industry can use the findings of the study to examine the staff self-efficacy by using the simplified items finalized in the structural model. Finally, the ability of the researcher to reach the target respondents during the short time was the major limitation of the study that could be used as the opportunity to the future researcher. Using other star-rated lodging establishments or hospitality segment, it will imply how critical uniform acts as the driver of self-efficacy to the front liners.